2017
DOI: 10.26864/v7n1.5
|View full text |Cite
|
Sign up to set email alerts
|

Gender-Based Violence, Coping Strategies and Perceived Social Support

Abstract: The phenomenon of gender-based violence is a very complex problem that occurs in multiple cultures. However, in recent decades, breaking the taboo that traditionally entailed violence against women has resulted in the visualization of the problem and increased social awareness. Several studies have highlighted the importance of coping strategies and the search for support to find a solution to end the abuse experienced by many women. This study aims to describe and analyze through the use of qualitative method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 3 publications
2
8
0
Order By: Relevance
“…Some women in this study also reported having accepted their “fate” and decided that there is nothing they can do about the abuse. This finding is consistent with other studies reporting that IPV survivors accepted what happened and what might happen to them ( 47 , 54 ). This form of response has also been identified as an emotion-focused strategy as it reconstructs the way a person looks at the problem situation rather than addressing the problem itself ( 19 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Some women in this study also reported having accepted their “fate” and decided that there is nothing they can do about the abuse. This finding is consistent with other studies reporting that IPV survivors accepted what happened and what might happen to them ( 47 , 54 ). This form of response has also been identified as an emotion-focused strategy as it reconstructs the way a person looks at the problem situation rather than addressing the problem itself ( 19 ).…”
Section: Discussionsupporting
confidence: 93%
“…Many coping responses of women in the present study were characterized by avoidance and distraction, which confirms previous research suggesting that women deal with the violence they experience by avoiding it or distracting themselves ( 47 , 54 , 55 ). A longitudinal study conducted in 2015 found that IPV survivors drank to cope with IPV ( 56 ).…”
Section: Discussionsupporting
confidence: 91%
“…The results of Waldrop and Resick's study showed that women victims of violence used avoidance coping strategies in the encounter of violence (Waldrop & Resick, 2004 ). The findings of another study showed that women in the face of violence have used avoidance‐oriented coping strategies with a focus on emotions (Pérez‐Tarrés et al., 2017 ). In selecting coping strategies to deal with violence, various factors and phenomena, such as the source of internal and external control, are effective.…”
Section: Discussionmentioning
confidence: 99%
“…In selecting coping strategies to deal with violence, various factors and phenomena, such as the source of internal and external control, are effective. If women do not have control over events, they will choose avoidance strategies based on their emotions that preclude them from opting for more impressive solutions to violence (Pérez‐Tarrés et al., 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…It seems that the level of perceived control over the situation, as well as the contextual factors that determine the level of change in the situation, are factors which have a great impact on the choice of the coping strategy used and its functionality ( Kacot, 2003 ; Puente-Martinez et al, 2021 ). In women victims of IPV, the cognitive avoidance strategy, understood as continuous attempts to keep the mind busy, spending time away from home, or distracting themselves with another activity, is frequently encountered, arguing that women resort to it in the face of a lack of controllability over the violent situation ( Walsh et al, 2011 ; Pérez-Tarrés et al, 2017 ; Ozturk et al, 2019 ). However, the use of this strategy has been shown to be moderated by other contextual factors such as the duration and frequency of violence ( Waldrop and Resick, 2004 ; Pérez-Tarrés et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%